How well are lesbians treated in UK fertility clinics?. (3rd July 2015) - Priddle, Helen
Abstract: Legislation regulating fertility treatment in the United Kingdom originally discouraged treatment without a father, resulting in many clinics denying access to lesbian couples. Lesbians now enjoy rights to legal union, dual parenthood and protection against discrimination. Consequently, increasing numbers seek fertility treatment. This is a growing stakeholder group, but it is unknown whether UK licensed centres are serving them adequately. Data from the Human Fertilisation and Embryology Authority suggests live birth rates after in vitro fertilisation for lesbians is comparable to estimates for natural attempt at pregnancy for heterosexuals, whereas success rates with donor insemination are lower. Unsurprisingly, live birth rates for lesbians after in vitro fertilisation are higher compared with heterosexual couples (the latter attending with fertility issues). However, outcomes for lesbians after donor insemination are slightly lower, potentially due to increased female age. Rather than adopting a one-heterosexual-size-fits-all approach, lesbian couples may benefit from new treatment pathways. They also have a different experience of fertility treatment, some reporting a wish to be presumed fertile rather than medicalised, and others encountering heterosexism by fertility professionals. Additionally, some lesbians with known fertility issues have needed to resort to legal action to obtain the publicly funded treatment they are entitled to.